Grain size effect on electrical properties of Ag6PS5I-based ceramic materials - Pogodin Artem; Погодін Артем; Shender Iryna; Шендер Ірина; Filep Mykhailo; Філеп Михайло; Filep Mihály; Oleksandr Kokhan; Кохан Олександр; Symkanych Olesya; Симканич Олеся; Malakhovska Tetyana; et al. (My University, 2022)
Abstract. Micro- and nanocrystalline powders were prepared by grinding of presynthesized Ag6PS5I in an agate mortar and a planetary ball mill, which were further investigated using XRD and SEM methods. Appropriate ceramic materials in the form of disks with a relative density of (91…94) ± 1% of the theoretical one were made using the cold pressing method for the obtained powders with subsequent annealing at the temperature 923 K. The values of the ionic and electron components of the total electrical conductivity were obtained analyzing the corresponding frequency dependences of the total electrical conductivity on the Nyquist plots using electrode equivalent circuits. It has been ascertained that reduction of crystallite sizes in Ag6PS5I-based ceramic materials leads to a slight increase in ionic conductivity and a significant increase in the electronic one, resulting in a decrease of the ratio between them.

Резюме. Шляхом розмелювання попередньо синтезованого Ag6PS5I в агатовій ступці та планетарному кульовому млині одержано мікро- та нанокристалічні порошки, які в подальшому досліджено з використанням методів XRD та SEM. Методом холодного пресування одержаних порошків з подальшим відпалом при температурі 923 K виготовлено відповідні керамічні матеріали у формі дисків з густиною (91…94) ± 1% від теоретичної. Значення іонної та електронної складових загальної електропровідності одержано шляхом аналізу відповідних частотних залежностей загальної електропровідності на діаграмах Найквіста з використанням еквівалентних схем електродів. Установлено, що зменшення розмірів кристалітів керамічних матеріалів, виготовлених на основі Ag6PS5I, приводить до незначного зростання іонної складової та суттєвого зростання електронної складової провідності, що викликає зменшення співвідношення між ними.
Вплив розмірів кристалітів на електричні властивості керамічних матеріалів на основі Ag6PS5I
Contents: http://journal-spqeo.org.ua/n3_2022/n3_2022_contents.htm Editorial board: http://journal-spqeo.org.ua/EditorialBoard.html
Keywords: argyrodite; superionic conductor; ceramics; impedance spectroscopy; electrical conductivity